Three days before the shooting-- - Ellison, Ralph. frey50; Callahan, John F., 1940-; Bradley, Adam. (New York : Modern Library, 2010)
Set in the frame of a deathbed vigil, this story is a multi generational saga centered on the assassination of the controversial, race-baiting U.S. senator Adam Sunraider, who's being tended to by "Daddy" Hickman, the elderly black jazz musician turned preacher who raised the orphan Sunraider as a light-skinned black in rural Georgia.
"The unfinished second novel"--Dust jacket.
Keywords: African American men -- Georgia; African Americans -- Georgia; Race relations